Education and training as a strategy to improve justification of medical imaging referrals in emergency departments - Sá dos Reis, Cláudia; Bennett, C.; Sun, Zhonghua (John Wiley & Sons, 2018)
Diagnostic imaging pathways are developed to ensure that medical imaging examinations are appropriately selected and referred by clinicians with the aim of justifying the use of imaging modalities for clinical diagnosis. Failing to comply with the imaging pathways or guidelines results in exposing patients to unnecessary ionising radiation due to malpractice of imaging referrals. This editorial provides a comment on a recent study reporting very high percentage of general x‐ray imaging referrals which did not or partially met the imaging pathways in an emergency department.